Pengaruh Ketinggian Tempat Terhadap Respon Termoregulasi Kambing Peranakan Etawah (PE): Effect of Altitude on Thermoregulatory Response of Etawah Grade Goat - Diana; Bagus Priyo Purwanto; Afton Atabany (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2016)
Etawah grade does were kept in different environment. Current research was conducted to compare the thermoregulatory response of Etawah grade goat which were kept at 200, 400 and 600 m asl. Measured environmental factors were temperature (Ta), relative humidity (Rh), and air velocity (Va) were measured for 12 hours from 06.00 am to 06.00 pm. Thermoregulatory response included rectal temperature (Tr), respiration rate (Rr) and heart rate (Hr) were measured every day at 6 am, 12 am and 6 pm. Data obtained were analyzed statistically using independent two-sample T-Test and regression analysis. The results showed different altitude 200, 400 and 600 m asl significantly affected (P<0.05) ambient temperature, which were average 30,16±2,88; 27,73±2,45 and 26,63±2,91; respectively. Otherwise, different altitude did not affect humidity and air velocity. Altitude significantly affected (P<0.05) rectal temperature and heart rate, but did not affect respiration rate. Etawah grade goat were comfortable to kept in 400 m asl.